(untitled) (Baghdad Science Journal, 2024)
The research was conducted to study the effect of different concentrations of nanoparticles (chitosan and titanium dioxide) of Fusarium oxysporum as elicitors to increase the production of active compounds from Salvadora persica callus. Determine the total flavonoids and alkaloids rustle that chitosan in 5 mg/L, titanium dioxide in 1 mg/L, and Fusarium oxysporum in 5 mg/L give 93.10 mg100mg, 128.7 mg/100mg, and 107.61 mg/100mg respectively whereas alkaloids give 2.39%, 3.91%, and 2.20 % respectively. The results showed superiority in the presence of flavonoids in the samples compared with alkaloids. HPLC (High-performance liquid chromatography) analysis shows significant differences in increasing flavonoid production (Rutin, Kaempferol, Quercetin, Catechin, Luteolin, and Apigenin) the addition of chitosan at 5 mg/L led to an increase in the production of Rutin, at 39.89mg/L. As for the induced callus treated with titanium dioxide at 1 mg/L, it increased Rutin to 35.89mg/L. While Rutin increased its production to 30.12 mg/L when treated with Fusarium oxysporum at 5 mg/l.